Space Invaders and Pedagogical Innovators: Regional Educational Understandings from Australian Occupational Travelers - Patrick Alan Danaher; Geoff Danaher; Beverley Moriarty (Journal of Research in Rural Education, 2003)
Australian occupational Travelers such as circus and fairground people often enter territories normally occupied by permanent residents. This article examines the ways in which these Travelers act as "space invaders," disrupting the boundaries between urban and rural, and as pedagogical innovators, when they develop pioneering approaches to their education. The findings indicate the efficacy of the concepts of multidimensionality, fluidity, and instability in analyzing and understanding the dynamics that occur between the occupational Travelers and permanent residents. The findings also demonstrate possibilities for educational provision that have been achieved for the children of one group of Australian occupational Travelers.